MICE tourism development in Swedish Lapland and the Barents Region : perspectives from tourism actors in Swedish Lapland - Gelter, Hans; Hellmér, Elisabeth; Gelter, Jennie (Luleå tekniska universitet, Medier ljudteknik och upplevelseproduktion och teater, 2012)
Godkänd; 2012; 20121031 (hage) BART - Offentligt - privat partnership inom Barents Regionen